1995
DOI: 10.2527/1995.7351424x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protein and(or) energy restriction in mares: plasma growth hormone, IGF-I, prolactin, cortisol, and thyroid hormone responses to feeding, glucose, and epinephrine1

Abstract: Sixteen light horse mares were fed diets of bermudagrass hay and a corn/cottonseed hull-based supplement formulated to contain either 100% (control) or 50% (restricted) of the protein and(or) energy requirements for maintenance in a 2 x 2 factorial arrangement of treatments. Plasma IGF-I, prolactin, cortisol, triiodothyronine, and thyroxine were monitored for 33 d. On the 27th d, frequent blood samples were drawn throughout the day for the measurement of growth hormone (GH), and on the 29th d, an epinephrine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(38 citation statements)
references
References 54 publications
4
33
1
Order By: Relevance
“…The results did not exclude the fact that some stress conditions such as stabling or Symbols indicate significant ( ▲ P < 0.05; ▲▲ P < 0.01) differences in average hormone compared to previous month management (Hoffman et al 1995;Malinowski et al 1996;Christensen et al 1997;Moons et al 2005) and diet (Messer et al 1995;Sticker et al 1995;Powell et al 2000) may determine higher T 4 , fT 3 and fT 4 concentrations in both barren and pregnant donkeys than data reported in horses. Stress conditions may be induced by blood drawing which was always performed in donkeys that were out to pasture.…”
Section: Discussionmentioning
confidence: 38%
“…The results did not exclude the fact that some stress conditions such as stabling or Symbols indicate significant ( ▲ P < 0.05; ▲▲ P < 0.01) differences in average hormone compared to previous month management (Hoffman et al 1995;Malinowski et al 1996;Christensen et al 1997;Moons et al 2005) and diet (Messer et al 1995;Sticker et al 1995;Powell et al 2000) may determine higher T 4 , fT 3 and fT 4 concentrations in both barren and pregnant donkeys than data reported in horses. Stress conditions may be induced by blood drawing which was always performed in donkeys that were out to pasture.…”
Section: Discussionmentioning
confidence: 38%
“…In our research, we recorded blood sampling times, and the multivariate analysis did not reveal significant differences in association with the time of blood extraction. Circulating concentrations of IGF-1, as well as GH, are clearly dependent on nutritional status in different species, including the horse (Philips, 1986;Thissen et al, 1994;Sticker et al, 1995;Christensen et al, 1997;Ropp et al, 2003). Restricted nutrition and dietary protein supply seem to be an important limiting factor for maximal stimulation of circulating IGF-1 concentrations (Sticker et al, 1995;Christensen et al, 1997;Ropp et al, 2003).…”
Section: Design Of the Studymentioning
confidence: 99%
“…Circulating concentrations of IGF-1, as well as GH, are clearly dependent on nutritional status in different species, including the horse (Philips, 1986;Thissen et al, 1994;Sticker et al, 1995;Christensen et al, 1997;Ropp et al, 2003). Restricted nutrition and dietary protein supply seem to be an important limiting factor for maximal stimulation of circulating IGF-1 concentrations (Sticker et al, 1995;Christensen et al, 1997;Ropp et al, 2003). In fact, it has been demonstrated that food deprivation leads to reduced blood concentrations of IGF-1, which are reversed following refeeding in humans (Clemmons et al, 1981), mice (McKnight and Goddard, 1989), rats (Maes et al, 1983), pigs (Dauncey et al, 1990) and horses (Sticker et al, 1995;Christensen et al, 1997).…”
Section: Design Of the Studymentioning
confidence: 99%
See 2 more Smart Citations